2011
DOI: 10.1017/s0007114511001322
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with oligonol, a low-molecular polyphenol derived from lychee fruit, attenuates diabetes-induced hepatic damage through regulation of oxidative stress and lipid metabolism

Abstract: We have identified the effects of oligonol, a low-molecular polyphenol derived from lychee fruit, on oxidative stress and lipid metabolism in a type 2 diabetic model. Oligonol was orally administered at 10 or 20 mg per kg body weight per d for 8 weeks to db/db mice, and its effects were compared with those of the vehicle in db/db and m/m mice. Serum and hepatic biochemical factors, and protein and mRNA expression related to lipid metabolism were measured. In the oligonol-administered group, there were signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 33 publications
0
58
0
Order By: Relevance
“…To avoid any intergroup differences in these indices, the rats were divided into three experimental groups: group 1, diabetic rats receiving water (n=5); groups 2 and 3, diabetic rats receiving 10 or 20 mg/kg body weight/day of oligonol (n=5, each group) through once-daily oral gavage. The administration dose and duration were determined based on other reports [12][13][14]. Rats that underwent a sham injection of citrate buffer without STZ were used as a nondiabetic control group (n=5).…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…To avoid any intergroup differences in these indices, the rats were divided into three experimental groups: group 1, diabetic rats receiving water (n=5); groups 2 and 3, diabetic rats receiving 10 or 20 mg/kg body weight/day of oligonol (n=5, each group) through once-daily oral gavage. The administration dose and duration were determined based on other reports [12][13][14]. Rats that underwent a sham injection of citrate buffer without STZ were used as a nondiabetic control group (n=5).…”
Section: Experimental Designmentioning
confidence: 99%
“…Kundu et al [10] reported the beneficial antioxidant and anti-inflammatory effects of oligonol in mouse skin, while Ahn et al [11] showed that oligonol protects against oxidative stress-induced inflammation in C6 glial cells. In our previous studies, oligonol improved hyperglycemia and hyperglycemia-induced oxidative stress in the liver and kidney of type 2 diabetic db/db mice, attenuated renal damage through the inhibition of glycation end product formation by glucose accumulation, and subsequently decreased NAD(P)H oxidase-derived ROS production in the kidney of db/db mice [12][13][14]. Therefore, oligonol appears to represent a novel therapeutic approach to a range of conditions associated with diabetes and hyperglycemia-related disorders such as oxidative stress and inflammation; however, the details of the mechanisms are still unknown.…”
Section: Introductionmentioning
confidence: 95%
“…Oligonol is a patented, low-molecular-weight polyphenol derived from lychee fruit (85%) and green tea (15% In another study carried out by Noh and group found that treatment of Oligonol(10 or 20 mg/kg) for 8 weeks to db/db mice reducedthe level of reactive oxygen species (ROS), lipid peroxidation, and the TAG and total cholesterol concentrations in both the serum and liver and attenuated oxidative stress through the inhibition of advanced glycation endproduct formation and its receptor expression 43 .…”
Section: Oligonolmentioning
confidence: 99%
“…Litchi is an edible fruit and is used in traditional medicine. As a traditional medicine, the fruit and its secondary metabolic products have been reported to have anticancer, anti-inflammatory, antifungal, antiviral, antioxidant, antiplatelet and anticoagulant, and antidiabetic activities [5,6,7,8,9,10,11,12].…”
Section: Introductionmentioning
confidence: 99%